75.3k views
3 votes
2x + y = 3 x - 2y = -1 If equation two is multiplied by -2 and then the equations are added, the result is _____. -3y = 3 3y = 5 5y = 5

User Gnebehay
by
5.7k points

2 Answers

1 vote

Answer:


5y=5

Explanation:


2x + y = 3


x - 2y = -1

If equation two is multiplied by -2, then the equation becomes


x - 2y = -1 times -2 becomes


-2x + 4y = +2

Now we add both equations


2x + y = 3


-2x + 4y = +2

----------------------------------


0 + 5y = 5


5y=5

User Jes
by
5.4k points
2 votes

Answer:

5y=5

Explanation:

Given equations

2x + y = 3 (i)

x - 2y = -1 (ii)

Multiplying equation (ii) by -2

Both sides of equation will be multiplies by -2.

-2(x-2y)= -2(-1)

The new equation will be

-2x+4y=2 => (iii)

Adding equation (iii) with equation (i), adding respective sides of both equations

(2x+y)+(-2x+4y)=3+2

2x+y-2x+4y=5

5y=5

So, after multiplying equation (ii) by -2 and then adding it to the first equation will give 5y=5

User Factorypolaris
by
5.1k points